Yeast biomass-induced Co2P/biochar composite for sulfonamide antibiotics degradation through peroxymonosulfate activation. (1st January 2021) - Peng, Yuanyuan; Tong, Wenhua; Xie, Yi; Hu, Wanrong; Li, Yonghong; Zhang, Yongkui; Wang, Yabo
Abstract: Advanced oxidation processes (AOPs) based on peroxymonosulfate (PMS) activation have attracted increasing attention in recent years for organic pollutants removal. Herein, we put forward a facile method to form cobalt phosphide/carbon composite for PMS activation. Combining impregnation approach with pyrolysis treatment enabled the formation of Co2 P/biochar composites using baker's yeast and Co 2+ as precursors. The as-synthesized products exhibited excellent catalytic activity for sulfamethoxazole (SMX) degradation over the pH range 3.0–9.0 b y activating PMS. For example, 100% of SMX (20 mg L −1 ) removal was achieved in 20 min with catalyst dosage of 0.4 g L −1 and PMS loading of 0.4 g L −1 . Near zero Co 2+ leaching was observed during catalytic reaction, which remarkably lowered the toxic risk of transition metal ion in water. Meanwhile, the reusability of catalyst could be attained by thermal treatment. SMX degradation intermediates were identified by liquid chromatography-mass spectrometry (LC-MS), which facilitated the proposal of possible SMX degradation pathways. Ecological Structure Activity Relationships (ECOSAR) analysis indicated that SMX degradation intermediates may not pose ecological toxicity to the environment. Further investigation verified that Co2 P/biochar composites could set off PMS activation not only for the degradation of SMX but also for other sulfonamides. In this study, we not only developed a facile method of utilizing environmental-benign biomass for transition metal phosphide/carbon composite formation, but also achieved highly efficient antibiotic elimination by PMS-based AOP. Graphical abstract: Image 1 Highlights: A facile impregnation-pyrolysis method is established to form Co2 P/biochar composite. Baker's yeast provides P and C element for Co2 P/biochar formation. Co2 P/biochar performs well for PMS activation to degrade sulfonamide antibiotics. Co 2+ leaching in catalytic reaction is low. Ecotoxicity of SMX and degradation intermediates is predicated by ECOSAR system.